Subpar Performance of the Mexican Economy in the NAFTA Era: Plausible Explanations. Issue 5 (19th October 2016) - Nguyen, Chu V.
ABSTRACT: Since 1994, the Mexican peso/U.S. dollar monthly real exchange rate conforms to the Purchasing Power Parity Theory. Evidently, Mexico has opened its economy and moved away from pre-NAFTA exchange rate interventionist policies. Mexico has tamed inflation—since 1999, the inflation rate has been stable relative to the U.S. inflation rate. Notwithstanding these impressive accomplishments, Mexico's real GDP growth rate has lagged behind that of several Latin American countries. It is likely that the perceived state of lawlessness has dampened foreign investment and tourism. Additionally, higher labor costs relative to China have adversely affected manufacturing sector exports.